Photosynthesis induction varies along the canopies of Zea mays and Sorghum bicolor: linking fast responses and non-photochemical quenching relaxation to biomass production - Almeida, Rafael L; Silveira, Neidiquele M [UNESP]; Sartori, Heitor L; Martins, Tamires S; Scarpari, Maximiliano S; Duarte, Aildson P; Sawazaki, Eduardo; Machado, Eduardo C; Ribeiro, Rafael V (Elsevier, 2025)
Light variability throughout the canopy requires sophisticated control for the induction of photosynthesis and deactivation of photoprotective mechanisms, which could optimize CO2 assimilation and crop yield. This study aimed to investigate the genotypic variation in photosynthesis induction and the relaxation of non-photochemical quenching (NPQ) across the canopy of five Zea mays and Sorghum bicolor cultivars. CO2 uptake, stomatal conductance, and NPQ dynamics were recorded every 60 s during photosynthetic induction. Initially, leaves at the top, middle and bottom canopy positions were dark-acclimated and subsequently exposed to irradiation of 2000 μmol m-2 s-1, for 1420 s. The Z. mays cultivar AG8701 showed the highest dry matter (335.7 ± 7 g plant-1) and the fastest light response across the canopy, reaching 85 ± 2 % of total CO2 uptake 700 s after induction (A700). This performance was attributed to the synchrony among CO2 assimilation, stomatal conductance, effective quantum efficiency of photosystem II, and fast NPQ deactivation. In contrast, S. bicolor cultivars exhibited weak and negative correlations (r = -0.27 to -0.46) between dry matter and photosynthetic traits. DKB560 was the slowest cultivar (A700 = 28 ± 7 %) for light response, exhibiting no NPQ relaxation throughout the canopy when light intensity varied. S. bicolor dry matter correlated with leaf area (r = 0.90), suggesting a compensatory mechanism for slower photosynthetic induction and NPQ relaxation. These findings provide valuable insights into breeding programs aiming to select new cultivars with higher photosynthesis, light responsiveness, and increased leaf area, key traits for higher yield.